Challenges and actions regarding the rehabilitation of degraded lands: case study from the the Pacific Island of Guam - Golabi, M.H.; Iyekar, C.; Denney, M. J. (Sociedade & Natureza, 2005)
Severely eroded lands of southern Guam are referred to as BadLands. These areactively eroding areas of very deep, well-drained saprolite derived from tuff and tuff breccia.These badlands are exposed to overland flow, wind and rain causing sever erosion as theresult of rapid runoff from the pitted, sloping sites void of vegetation. Through soil removalor sediment transport, erosion also alters the inherent physical and chemical properties ofthese soils. This alteration resulted in degradation, in turn affecting the environment as wellas water quality in the down stream. The on-site damage from erosion is indeed a problem toenvironmental ecosystem of the island. Sediment lost due to erosion clogs rivers, lakes, andwaterways. It reduces the water storage capacity of reservoirs and canals and increasesflooding.The challenge facing soil and environmental scientists is to develop conservation andrestoration strategies at the farm as well as at the watershed level that address crop productionand natural resources protection needs, within a framework of increasing environmental andfinancial constraints. In our soil conservation program at the College of Natural and AppliedSciences of the University of Guam we have adopted integrated approaches to evaluate avariety of strategies, including the effect of conservation tillage and residue management,crop rotation with leguminous plants (sunnhemp) as green manure as well as the use ofcomposted organic wastes as soil amendment for organic matter build up, all for soilrehabilitation and restoration of the badlands in southern Guam. In a companion study we areevaluating the effectiveness of Vetiver technology as a sediment trap to mitigate sedimenttransport in a typical watershed basin in southern Guam. This paper discusses themethodology as well as up to date data that shows the effect of Vetiver technology onsediment trapping at the watershed level.